Search for Higgs boson production in association with a high-energy photon via vector-boson fusion with decay into bottom quark pairs at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector - The ATLAS collaboration; G. Aad; B. Abbott; D. C. Abbott; A. Abed Abud; K. Abeling; D. K. Abhayasinghe; S. H. Abidi; O. S. AbouZeid; N. L. Abraham; H. Abramowicz; H. Abreu; et al. (Journal of High Energy Physics, 2021)
Abstract A search is presented for the production of the Standard Model Higgs boson in association with a high-energy photon. With a focus on the vector-boson fusion process and the dominant Higgs boson decay into b-quark pairs, the search benefits from a large reduction of multijet background compared to more inclusive searches. Results are reported from the analysis of 132 fb −1 of pp collision data at s $$ \sqrt{s} $$ = 13 TeV collected with the ATLAS detector at the LHC. The measured Higgs boson signal yield in this final-state signature is 1.3 ± 1.0 times the Standard Model prediction. The observed significance of the Higgs boson signal above the background is 1.3 standard deviations, compared to an expected significance of 1.0 standard deviations.